Impact of COVID-19: nursing perspective and concern - Sharma, Rakesh; S., Vishwas A.; Jelly, Prasuna (International Journal Of Community Medicine And Public Health, 2020)
The Nurses' contribution to the Health care sector globally is always delightful. The abrupt and undetected spread of Coronavirus disease 2019 (COVID-19) worldwide, with variant mortality and morbidity rates in different countries, had put the health system into crisis. Response to the outbreak, preventing the spread of infection and control strategies, and nursing care during the pandemic is vital to attain goals of present medical emergency. Authors took efforts to discuss the perspective of nurses being front line health care workers, in an imperative situation in which the human population is undergoing with uncertainty, along with issues and concerns involved in managing the situation. The leadership qualities among nurses to overcome the complex COVID-19 is once again proved in this episode of the pandemic. The concern to individual nurse in preserving the ethical and moral values with the fundamental framework and training undergone is recalled and channelized. Nurses play an essential job responsibility in numerous ways while dealing with mankind, sick or well; either in a health care setting or at the community level. Vital domains involved in full filling nurses role during pandemic (COVID-19) noticeably creating awareness, screening services, and support for the general public who are high-risk conditions, infection prevention and surveillance, implementing appropriate preparations and precautions in health care settings, protecting the patients with immunodeficient and or co-morbidities, care of COVID-19 patients with acute and chronic illness.